Happiness, positive emotions, and subjective well-being in dementia - Miklitz, Carolin; Fliessbach, Klaus; McCormick, Cornelia (Frontiers in Neurology, 2024)
Research on non-cognitive features of dementia traditionally focusses on neuropsychiatric symptoms and challenging behavior and thus on negative aspects of the disease. Despite the clinical observation that many patients frequently report subjective well-being and often express positive emotions there is only little research on the definition, measurement and determinants of subjective well-being and happiness in people living with dementia. Furthermore, the few studies there are, examined happiness using retrospective questionnaires and the accounts of relatives or caregivers. However, in dementia, the experiencing self becomes more significant since past and future thinking are fading into the background. Here, we review the relative scarce literature in this field, discuss different psychological constructs and their applicability for dementia research, and suggest methods for measuring the addressed constructs in people with dementia. In particular, we propose methodology to study happiness and positive emotions in the experienced moment of the participants using ecological momentary assessments (EMA). We believe that adequate measures of momentary subjective well-being might become an important outcome parameter in clinical dementia trials beyond the currently used quality of life measures.